Leniency Bias in Performance Ratings: The Big-Five Correlates - Cheng, Kevin H. C.; Hui, C. Harry; Cascio, Wayne F. (Frontiers in Psychology, 2017)
Some researchers assume that employees’ personality characteristics affect leniency in rating others and themselves. However, little research has investigated these two tendencies at the same time. In the present study we developed one index for other-rating leniency and another one for self-rating leniency. Based on a review of the literature, we hypothesized that a generous assessment of peers would more likely be made by those who are extroverted and agreeable than by those who are not. Furthermore, a generous assessment of oneself would more likely be made by people who are conscientious and emotionally stable, than by people who are not. We also investigated if the leniency in rating others and the leniency in rating oneself are part of a more general leniency tendency. Data collected from a sample of real estate dealers provided support for the above hypotheses. Limitations and implications for future research are discussed.